Universality of stable multi-cluster periodic solutions in a population model of the cell cycle with negative feedback. (1st January 2021) - Prathom, Kiattisak; Young, Todd R.
Abstract : We study a population model where cells in one part of the cell cycle may affect the progress of cells in another part. If the influence, or feedback, from one part to another is negative, simulations of the model almost always result in multiple temporal clusters formed by groups of cells. We study regions in parameter space where periodic ' k -cyclic' solutions are stable. The regions of stability coincide with sub-triangles on which certain events occur in a fixed order. For boundary sub-triangles with order ' r s 1 ', we prove that the k -cyclic periodic solution is asymptotically stable if the index of the sub-triangle is relatively prime with respect to the number of clusters k and neutrally stable otherwise. For negative linear feedback, we prove that the interior of the parameter set is covered by stable sub-triangles, i.e. a stable k -cyclic solution always exists for some k . We observe numerically that the result also holds for many forms of nonlinear feedback, but may break down in extreme cases.